The Era of Buying Green Exploring Determinants of Green Purchase Intentions - Sanli, Dilara (My University, 2026)
The increasing importance of environmental sustainability has led to growing interest in un-derstanding the factors that influence consumers’ green purchase intentions. As consumers are becoming more aware of environmental issues, companies in the fast-moving consumer goods (FMCG) sector are increasingly introducing environmentally friendly products and marketing strategies to address this demand. Despite the growing popularity of green products, consum-ers’ willingness to purchase such products remains influenced by a variety of factors. Therefore, the purpose of this study is to examine the determinants of consumers’ green purchase inten-tions and to compare these determinants between Germany and Finland. The study is based on the Theory of Planned Behaviour and incorporates twelve determinants that have been identi-fied in previous literature as relevant predictors of green purchase intentions. These determi-nants include green advertising, eco-packaging and green ingredients, perceived price, envi-ronmental knowledge and concern, health consciousness, perceived value and quality, demo-graphic characteristics, corporate green image, green self-identity, attitude towards green products, subjective norms, and prior experience with green products. A quantitative research approach has been adopted. Data have been collected through an online questionnaire dis-tributed among consumers in Germany and Finland. After data cleaning, a final sample of 193 respond-ents has been obtained. The collected data have been analysed using reliability analy-sis and multiple regression analysis to examine the relationships between the selected deter-minants and consumers’ green purchase intentions. The findings indicate that green purchase intentions are influenced by a combination of product-related, psychological, social, and demo-graphic factors. Environmental knowledge and concern, health consciousness, per-ceived price, and attitude towards green products have been identified as important determi-nants in both countries. At the same time, several country-specific differences have been ob-served. Green advertising, eco-packaging and green ingredients, and prior experience with green products have been found to influence green purchase intentions only among German consumers, whereas perceived value and quality as well as green self-identity have been found to influence green purchase intentions only among Finnish consumers. The findings further suggest that psychological and product-related factors are more influential than demographic characteristics. The study contributes to the existing literature by providing a comparative analysis of green purchase intentions in Germany and Finland and by integrating twelve deter-minants within a single conceptual framework. The findings also provide practical implications for companies operating in the FMCG sector.
Keywords: consumer behaviour; green products; green economy; sustainable consumption; sustainable development; environmental responsibility; consumers; environmental awareness; products; marketing; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Hallintotieteiden maisteriohjelma|en=Master's Programme in Administrative Sciences|